Impact of a 3-Month Recall Using High-Fidelity Simulation or Screen-Based Simulation on Learning Retention During Neonatal Resuscitation Training for Residents in Anesthesia and Intensive Care: Randomized Controlled Trial - Anne-Claire Louvel; Cécile Dopff; Gauthier Loron; Daphne Michelet (JMIR Serious Games)
Abstract BackgroundRetention capacities are dependent on the learning context. The optimal interval between two learning sessions to maintain a learner’s knowledge is often a subject of discussion, along with the methodology being used. Screen-based simulation could represent an easy alternative for retraining in neonatal resuscitation. ObjectiveThe aim of the study was to evaluate the benefits of a 3-month recall session using high-fidelity simulation or screen-based simulation, assessed 6 months after an initial neonatal resuscitation training session among anesthesia and intensive care residents. MethodsAll participating anesthesia and intensive care residents were volunteers, and they underwent training in the same session, which included a theoretical course and high-fidelity simulation. The attendees were then randomized into three groups: one with no 3-month recall, one with a high-fidelity simulation recall, and one with a screen-based simulation recall. To reassess the skills of each participant, a high-fidelity simulation was performed at 6 months. The primary outcomes included expert assessment of technical skills using the Neonatal Resuscitation Performance Evaluation score and nontechnical skills assessed by the Anesthesia Non-Technical Skills score. Secondary outcomes included a knowledge quiz and self-assessment of confidence. We compared the results between groups and analyzed intragroup progressions. ResultsTwenty-eight participants were included in the study. No significant differences were observed between groups at the 6-month evaluation. However, we observed a significant improvement in theoretical knowledge and self-confidence among students over time. Regarding nontechnical skills, as evaluated by the Anesthesia Non-Technical Skills score, there was significant improvement between the initial training and the 6-month session in both recall groups (16 vs 12.8, PPPP ConclusionsInitial neonatal resuscitation training for anesthesia and intensive care residents leads to improved knowledge and self-confidence that persist at 6 months. A 3-month recall session, whether through high-fidelity simulation or screen-based simulation, improves nontechnical skills (eg, situation management and team communication) and technical skills. Screen-based simulation, which saves time and resources, appears to be an effective educational method for recall after initial training. The study outcomes justify the need for further studies with larger sample sizes to confirm the promising role of serious games in educational programs for medical students.